Stem cells: Hype or Miracle Cure? - SYED MOHAMMAD ASIM HUSSAIN, SEEMEEN HUSSAIN, (Journal of Fatima Jinnah Medical University, 2018)
Objective: This review aims to evaluate whether stem cell therapy is a miracle cure or hype The analysis will include the proliferation, differentiation, problems, developments and applications of stem cells in a sequential manner. Study Design: Analytical Subjects and Methods: This review uses a dialectical approach to objectively assess the therapeutic potential of stem cells. The physico-chemical interactions that underpin the generation, maintenance and differentiation of stem cells are studied. Associated problems and developments in stem cell therapy are compared to understand its current and future applications. Results and Conclusion: This article suggests that stem cell therapy will be ultimately beneficial. However, it is premature to give a timeline. While it certainly has great potential, the difficulties of practical application must be overcome before it can be called a miracle cure.